MEASURES TO PREVENT THE SPREAD AND PREVENTION OF NON-INFECTIOUS BRONCHIONECROSIS OF FISH - Yunusov Kh.B. d.s.c., professor.; Kurbanov F.I., PhD.; Kubaev Z.; Mamarasulova D.; Khushnazarova M.; Ollaberganova R. (Western European Studies, 2024)
There are 2 types of non-infectious bronchionecrosis in fish: exogenous and endogenous. Analysis of the literature on the chronic impact of adverse environmental factors on fish as the main cause of non-infectious bronchionecrosis in fish
Keywords: Bronchonecrosis; exogenous and endogenous; organic acids; macrophytes